Meta-Analysis Reveals Reduced Coral Calcification Under Projected Ocean Warming but Not Under Acidification Across the Caribbean Sea - Bove, Colleen B.; Umbanhowar, James; Castillo, Karl D. (Frontiers in Marine Science, 2020)
Ocean acidification and warming are two of the many threats to coral reefs worldwide, and Caribbean reef-building corals are especially vulnerable. However, even within the Caribbean, experimental acidification and warming studies reveal a wide array of coral calcification responses across reef systems and among species, complicating efforts to predict how corals will respond to these global-scale stressors. We conducted a meta-analysis to investigate the calcification responses of Caribbean corals to experimentally induced seawater ocean acidification, ocean warming, and the combination of both stressors. Calcification rates were reduced for corals reared under warming alone, but acidification and the combination of both stressors did not clearly reduce calcification rates. Calcification responses of corals collected from the Florida Keys and Belize were compared for regional differences since a greater number of studies were performed on corals collected from these two regions. Notably, corals from the Florida Keys did not exhibit reduced calcification under acidification, warming, or the combination of both stressors, while corals from Belize exhibited reduced calcification under warming alone. Further investigation of these regional trends suggests that the warming and acidification treatments employed dictated calcification responses, rather than collection region. Results from this meta-analysis are constrained by the very few studies that have been conducted within the Caribbean to assess ocean acidification and warming and the large variation in experimental procedure among studies. This meta-analysis reveals existing gaps in our understanding of how corals will likely respond to projected acidification and warming and highlights ways to improve comparability among experimental studies conducted on corals within the same region to better predict coral calcification response under global change.